IMF Survey, Volume 31, Issue 20. (IMF Survey; IMF Survey, 2002)
The IMF has added its voice to the debate over the euro area's Stability and Growth Pact (SGP), urging the three largest countries-France, Germany, and Italy-to rein in their fiscal deficits. It also trimmed its economic growth forecasts for the 12-nation monetary union and urged the European Central Bank (ECB) to adopt a bias toward lowering interest rates.